Student youth: Motives for higher professional education and views on employment factors (Herald of Journalism, 2018)
Issues of students’ professional preferences reflect and are closely related to the perception, representationand priorities of youth in the field of work. The development of these issues leads to the solution of importantpractical problems, reveals the trends and content of the professional activity of the younger generationand determines the degree of its involvement in society and social relations. The study of these problemsis especially important for the generation of students who are currently studying the basics of professionalknowledge, and in the next two-three years will enter the labor market and become the productive force of aISSN 1563-0242 Herald of journalism. №1 (47). 2018 89Тaжинa Г.О., Исaевa Н.С.society. A young generation that meets the requirements of the time, tries to combine their learning with workin various spheres of the economy. It is during the acquisition of a profession and entry into the labor marketyoung people to develop ideas about the goals of their professional activities and how to achieve them, whichaffect their motivation, career orientations and strategies. In this regard, the need for a comprehensive studyof students’ job attitudes is obvious, as in the near future today’s students will occupy key positions in theeconomy of the country. The article examines the motives for choosing majors in higher education by youngpeople and their understanding of social-psychological factors affecting the employment of youth. Timelydetermination of these factors, informational and psychological support in professional self-determinationgreatly help in the building of a socially mature personality with a conscious goal setting, responsible for itsactivities and behavior in professional and civic self-actualization. The article reflects the results of socialpsychologicalresearch within the grant project framework of the Non-Commercial Joint-Stock Association“Center for Support of Civil Initiatives” implemented by the Public Association “Innovative Practices”.Key words: motives for choosing a profession, employment of young people, professional preferences,higher education major.